Management Analysis At Pematangsiantar Swimming Club - Wahyu Ade Putra; Benny Aprial; Eka Abdurrahman (Sekolah Tinggi Olahraga & Kesehatan Bina Guna, 2024)
Swimming is one of the sports that has many fans in Indonesia. Indonesia. Pematangsiantar City also has the potential to develop swimming sports. This club has an important role in developing local swimming athletes and facilitating the community in channeling their interests. and facilitates the community in channeling their interests and talents in swimming. and talents in the sport of swimming. The purpose of this study is to provide a significant contribution in improving the performance and management of swimming sports at Pope Aquatic Swimming Club Pematangsiantar City. The method used is qualitative research with case study approach. The data analysis technique used is the Miles and Huberman model. Pematangsiantar Aquatic Club Pematangsiantar City has a good organizational structure, with administrators who also play a role in providing direction and coordination to coaches. also plays a role in providing direction and coordination to the coach and actively involved in coaching athletes. Club funds are managed with managed well even through one door, and training facilities are adequate and well maintained. adequate and well maintained. Competent, experienced coaches and able to help athletes to achieve. Although there is no special budget for non-training activities, management still pays attention to the welfare and rewards for athletes who excel. pay attention to the welfare and appreciation of athletes who excel.